2016
DOI: 10.1139/cjz-2016-0098
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the behavioural responses of wild marine mammals to noise: the disparity between science and policy

Abstract: Noise can cause marine mammals to interrupt their feeding, alter their vocalizations, or leave important habitat, among other behavioural responses. The current North American paradigm for regulating activities that may result in behavioural responses identifies received levels (RL) of sound at which individuals are predicted to display significant behavioural responses (often termed harassment). The recurrent conclusion about the need for considering context of exposure, in addition to RL, when assessing prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 114 publications
0
84
0
1
Order By: Relevance
“…Effects of whale-watching activities on surface and diving patterns were particularly notable when vessels occurred within 400 m of the whales, but were perceptible when vessels were at distances up to 1000 m. Behavioural responses of blue whales in this study were of a larger magnitude compared to those documented in fin and minke whales from other areas (Stone et al 1992, Christiansen et al 2013a, suggesting that this population might be particularly sensitive to disruptive activities when animals are foraging. Recent reviews of behavioural responses of marine mammals to various sources of anthropogenic noise and activity have concluded that behavioural response is highly context-specific (Gill et al 2001, Southall et al 2007, Ellison et al 2012, Gomez et al 2016). There is a need to investigate whether foraging depth and frequency of exposure to vessels affect the behavioural response of blue whales (Laist et al 2001, Goldbogen et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of whale-watching activities on surface and diving patterns were particularly notable when vessels occurred within 400 m of the whales, but were perceptible when vessels were at distances up to 1000 m. Behavioural responses of blue whales in this study were of a larger magnitude compared to those documented in fin and minke whales from other areas (Stone et al 1992, Christiansen et al 2013a, suggesting that this population might be particularly sensitive to disruptive activities when animals are foraging. Recent reviews of behavioural responses of marine mammals to various sources of anthropogenic noise and activity have concluded that behavioural response is highly context-specific (Gill et al 2001, Southall et al 2007, Ellison et al 2012, Gomez et al 2016). There is a need to investigate whether foraging depth and frequency of exposure to vessels affect the behavioural response of blue whales (Laist et al 2001, Goldbogen et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on deep sea fish reveal that some species communicate using low sound frequencies (<1.2 kHz; Rountree et al, 2011) and it is thought that other benthic species may use sensitive acoustic systems to detect food falls up to 100 m away (Stocker, 2002). Anthropogenic noise is known to impact a number of fish species and marine mammals by inducing behavior changes, masking communication, and causing temporary threshold-shifts in hearing or permanent damage depending on the species, type of noise and received level (Gomez et al, 2016;Nedelec et al, 2017).…”
Section: Increased Noisementioning
confidence: 99%
“…bycatch, predation) is also a major consideration when evaluating potential harm. If animals are strong ly motivated to stay in an area because of its biological importance, this does not mean there are no dele terious effects on their physiology (Gill et al 2001, Beale & Monaghan 2004, Wright et al 2007, Aguilar de Soto & Kight 2016, Gomez et al 2016 A more comprehensive paradigm for assessing impacts of anthropogenic noise (or other activities) on marine mammals needs to include explicit consideration of all potential pathways of harm, including adverse impacts resulting from both close-range exposure and displacement away from the sound source. Both types of responses can lead to reduced foraging success, increased stress, disruption of important social and reproductive functions, and decreased survival or reproductive success through a variety of pathways (Fig.…”
Section: Change In Paradigmmentioning
confidence: 99%
“…6). Permanent and temporary threshold shifts have often been the primary consideration for regulatory measures and are more likely for animals that may be reluctant to leave an area, but stress (Rolland et al 2012), effects of acoustic 'masking' (Todd et al 1996, Clark et al 2009, Nielsen et al 2012, Gomez et al 2016) and displacement (e.g. Dähne et al 2013, Thompson et al 2013) are increasingly recognized as important impacts that need to 403 Fig.…”
Section: Change In Paradigmmentioning
confidence: 99%
See 1 more Smart Citation